Biofunctionalization of Microgroove Surfaces with Antibacterial Nanocoatings. (17th June 2020) - Lai, Yingzhen; Xu, Zhiqiang; Chen, Jiang; Zhou, Renbin; Tian, Jumei; Cai, Yihuang
Abstract : Objectives . To investigate the physical properties of the modified microgroove (MG) and antibacterial nanocoated surfaces. In addition, the biological interactions of the modified surfaces with human gingival fibroblasts (HGFs) and the antibacterial activity of the surfaces against Porphyromonas gingivalis were studied. Methods . The titanium nitride (TiN) and silver (Ag) coatings were deposited onto the smooth and MG surfaces using magnetron sputtering. A smooth titanium surface (Ti-S) was used as the control. The physicochemical properties including surface morphology, roughness, and hydrophilicity were characterized using scanning electron microscopy, atomic force microscopy, and an optical contact angle analyzer. The "contact guidance" morphology was assessed using confocal laser scanning microscopy. Cell proliferation was analyzed using the Cell Counting Kit-8 assay. The expression level of the main focal adhesion-related structural protein vinculin was compared using quantitative reverse transcription PCR and Western blotting. The antibacterial activity against P . gingivalis was evaluated using the LIVE/DEAD BacLight™ Bacterial Viability Kit. Results . The Ag and TiN antibacterial nanocoatings were successfully deposited onto the smooth and MG surfaces using magnetron sputtering technology. TiN coating on a grooved surface (TiN-MG) resulted in less nanoroughness and greater surface hydrophilicity than Ag coating on a smooth surface (Ag-S), which was more hydrophobic. Cell proliferation and expression of vinculin were higher on the TiN-MG surface than on the Ag-coated surfaces. Ag-coated surfaces showed the strongest antibacterial activity, followed by TiN-coated surfaces. Conclusion . Nano-Ag coating resulted in good antimicrobial activity; however, the biocompatibility was questionable. TiN nanocoating on an MG surface showed antibacterial properties with an optimal biocompatibility and maintained the "contact guidance" effects for HGFs.